Study of Minangkabau Vocabulary in the Tanjung Barulak Manuscript: A Study of Malay Arabic Script - Rudiamon, Septika; Diana, Marisya Putri; Aulia, Manisha; Pahutar, Elisah; Jafar, Muslim (Mantiqu Tayr: Journal of Arabic Language, 2025)
Minangkabau manuscripts in Arabic Malay script contain many Minang vocabulary that is rarely revealed, even the vocabulary is rarely used in everyday language in Minangkabau due to the acculturation of the language into Indonesian. This paper aims to present Minangkabau vocabulary in Arabic Malay script in the Tanjung Barulak manuscript of Tanah Datar district, and to reveal the meaning of Minangkabau vocabulary in accordance with the development of the Indonesian language. This study uses a qualitative approach with a philological research method that has six working steps, namely manuscript inventory, manuscript description, manuscript grouping and text comparison, selection of text edition methods, transliteration, and additional studies (text comments). The primary data source is the Tanjung Barulak manuscript with the code 02/BB.II/twf/2021, and the secondary data source is in the form of literature studies from scientific articles, books, and several other related sources. The results of this study found more than 100 Minangkabau vocabulary in Arabic Malay script in the Tanjung Barulak manuscript. In addition, the meaning of the Minangkabau vocabulary in Arabic Malay script in this Manuscript is mostly far different from the development of the Indonesian language which already uses the General Guidelines for Indonesian Spelling, there are even some Minangkabau vocabulary that is no longer used in communication by the Minangkabau people due to language and cultural shifts. This study has presented several Minang vocabularies that are rarely used in daily communication found in one of the Minangkabau manuscripts. It is hoped that other researchers will continue to dig deeper into the Minangkabau vocabulary that found in Minangkabau manuscripts in order to enrich the treasury of the Minangkabau regional language.